-2(x+2)+3x=x

Simple and best practice solution for -2(x+2)+3x=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x+2)+3x=x equation:



-2(x+2)+3x=x
We move all terms to the left:
-2(x+2)+3x-(x)=0
We add all the numbers together, and all the variables
2x-2(x+2)=0
We multiply parentheses
2x-2x-4=0
We add all the numbers together, and all the variables
-4!=0
There is no solution for this equation

See similar equations:

| 14=h/6+8 | | 399+x=413 | | 4x-2=x-18 | | X=20.17647059+(-0.8235294118y | | v-9/3=9 | | -60=4(1+4v) | | 20/x2−5=−3 | | -6(-6n+2)=-288 | | 2x-1+x+1=180 | | (8-k)/5=6 | | 8-k/5=2 | | 1/2(2-4x)2x=13 | | -5=5+z | | 0.15=y-0.450.15 | | 3p/12=6 | | 6m+3+9=2m-6-m | | -3+5y=-38 | | 4-3x/3=7 | | 4k-21=65 | | y/30-21=39 | | 7=2f | | (2x+3)(2x+5)=(2x+3)(2x+5) | | 84=6(c-81) | | 8x+1=3x×20 | | (2x+3)(2x+5)=x | | 90=9(u+8) | | -14=-20=n | | 9(r-91)=18 | | -16=-17+m | | z/6+32=36 | | 20-2w=6 | | 3.56+7.56x+9.12=50.85 |

Equations solver categories